2022
DOI: 10.1051/0004-6361/202141645
|View full text |Cite
|
Sign up to set email alerts
|

Spi-OPS: Spitzer and CHEOPS confirm the near-polar orbit of MASCARA-1 b and reveal a hint of dayside reflection

Abstract: Context. The light curves of tidally locked hot Jupiters transiting fast-rotating, early-type stars are a rich source of information about both the planet and star, with full-phase coverage enabling a detailed atmospheric characterisation of the planet. Although it is possible to determine the true spin–orbit angle Ψ – a notoriously difficult parameter to measure – from any transit asymmetry resulting from gravity darkening induced by the stellar rotation, the correlations that exist between the transit parame… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 131 publications
0
7
1
Order By: Relevance
“…Likewise, using the H 2 O signal, we obtain K p = 197.8 ± 3.5 and 194.9 ± 3.0 km s −1 , respectively. These values are somewhat different from 204.2 ± 0.2 km s −1 , as calculated using parameters from Hooton et al (2022). Our detection of emission features of CO and H 2 O requires the presence of a temperature inversion in the dayside atmosphere of MASCARA-1 b.…”
Section: Molecular Detectionscontrasting
confidence: 64%
See 2 more Smart Citations
“…Likewise, using the H 2 O signal, we obtain K p = 197.8 ± 3.5 and 194.9 ± 3.0 km s −1 , respectively. These values are somewhat different from 204.2 ± 0.2 km s −1 , as calculated using parameters from Hooton et al (2022). Our detection of emission features of CO and H 2 O requires the presence of a temperature inversion in the dayside atmosphere of MASCARA-1 b.…”
Section: Molecular Detectionscontrasting
confidence: 64%
“…To demonstrate the on-sky performance of CRIRES+ for exoplanet atmospheric characterization, we conduct a case study of the UHJ MASCARA-1 b (Talens et al 2017;Hooton et al 2022). Previous transmission spectroscopy studies in the optical have found no chemical signatures in the planet's atmosphere (Stangret et al 2022); these studies were made particularly difficult due to the strong Rossiter-McLaughlin effect when searching for key atomic species.…”
Section: Results: a Case Study Of Mascara-1 Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the rapid rotational rate of HD 56414, we might expect to see an asymmetrical transit profile due to gravity darkening, which can be modeled to independently measure the true spin-orbit angle (Ψ; Barnes 2009). To test this, we also fit the TESS light curve to a gravity-darkened model following Hooton et al (2022) in which we additionally fit for the stellar inclination (i å ) and sky-projected stellar obliquity (λ). We fixed the stellar polar temperature, stellar equatorial radius, and  v i sin to the median values in Table 1, and fixed the gravitydarkening coefficient β according to Claret (2017).…”
Section: Planet Model Fitmentioning
confidence: 99%
“…One of the main themes of its science program is the characterization of exoplanet atmospheres (Benz et al 2021). This consists of observations of secondary eclipses of hot Jupiters (e.g., Lendl et al 2020;Hooton et al 2022) across a wide range of temperatures and planetary surface gravities, full or partial phase curves of the most compelling targets (e.g., Deline et al 2022), and detailed observations of ultra-hot super-Earths (e.g., Morris et al 2021).…”
Section: Introductionmentioning
confidence: 99%